Development of nitazoxanide-loaded colon-targeted formulation for intestinal parasitic infections: centre composite design-based optimization and characterization - Charu Bharti; Upendra Nagaich; Jaya Pandey; Suman Jain; Neha Jain (SpringerOpen, 2020)
Abstract Background The current investigation is focused on the development and characterization of Eudragit S100 coated nitazoxanide-loaded microbeads as colon-targeted system utilizing central composite design (CCD) and desirability function. The study initiated with the selection of a BCS class II drug nitazoxanide and its preformulation screening with excipients, selection of polymer and identification of concentration for CCD, selection of optimized formulation based on desirability function, and in vitro release studies in simulated gastric and colonic media and stability studies. A two-factor, three-level CCD was employed with two independent variables, i.e. X1 (chitosan % w/v) and X2 (sodium tripolyphosphate % w/v), and three dependent variables, i.e. Y1 (particle size in micrometres), Y2 (percentage yield) and Y3 (percent entrapment efficiency), were chosen. Additionally, surface morphology, mucoadhesion and in vitro drug release studies were also conducted. Result Chitosan concentration showing maximum entrapment and optimum particle size was selected to formulate chitosan beads. The polynomial equation and model graphs obtained from the Design-Expert were utilized to examine the effect of independent variables on responses. The effect of formulation composition was found to be significant (p ˂ 0.05). Based on the desirability function, the optimized formulation was found to have 910.14 μm ± 1.03 particle size, 91.84% ± 0.64 percentage yield and 84.75% ± 0.38 entrapment efficiency with a desirability of 0.961. Furthermore, the formulations were characterized for in vitro drug release in simulated colonic media (2% rat caecal content) and have shown a sustained release of ∼ 92% up to 24 h as compared to in vitro release in simulated gastric fluid. Conclusion The possibility of formulation in enhancing percentage yield and entrapment efficiency of nitazoxanide and the utilization of CCD helps to effectively integrate nitazoxanide microbeads into a potential pharmaceutical dosage form for sustained release.